Correlation of Total Lipid Content of Chlorella vulgaris With the Dynamics of Individual Fatty Acid Growth Rates - Moradi-Kheibari, Narges; Ahmadzadeh, Hossein; Lyon, Stephen R. (Frontiers in Marine Science, 2022)
Microalgae are considered as a promising feedstock for the production of valuable fatty acids. In this study, individual fatty acid profiles during the growth period of C. vulgaris were investigated. The results showed the quantity and the type of fatty acids changed with varying rates during the growth of microalgal cells. Interchanging the fatty acid profiles may provide some metabolic information as a complimentary method to radiolabeling studies. For C. vulgaris, two unsaturated fatty acids, oleic and linoleic acids were the major components. Constant concentration of palmitic and oleic acids show they may serve as precursors for longer chain fatty acids. Higher concentration of palmitic rather than palmitoleic acids (About 16 to 34 times depending on the cultivation day) shows that palmitic acid production rate is higher than its conversion rate to longer chain fatty acids. In fact palmitoleic acid might have been partly converted to oleic and linoleic acids. The fatty acids content variations during the growth period are not linear and can be fitted to a Sigmoidal model with R2 value higher than 0.98 and low RMSD values (except for oleic and palmitic acid).